Structure and microhardness of low pressure polymerized fullerite C60 - Isakina, A. P.; Lubenets, S. V.; Natsik, V. D.; Prokhvatilov, A. I.; Strzhemechny, M. A.; Fomenko, L. S.; Aksenova, N. A.; Soldatov, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We have carried out low-temperature x-ray diffraction studies on C60 fullerite polymerized by low quasi-hydrostatic pressure of 1.1 GPa at T = 563 K. It is established that at room temperature in freshly prepared samples three phases mainly coexist, viz. a compressed cubic phase with the lattice parameter a = 13.94 Angstrem , an orthorhombic O` phase with the lattice parameters a = 9.12 Angstrem , b = 9.82 Angstrem, c = 14.60 Angstrem, and a rhombohedral phase of symmetry R3m with the parameters a = 9.20 Angstrem and c = 24.27Angstrem. Mechanical grinding or annealing at 573 K entails depolymerization of sintered samples and restoration of the fcc structure of pristine C60. During annealing in air, intercalation of fullerite lattice by oxygen molecules occurs as well as a substantial amount of some new phase is formed, most probably with tetragonal symmetry, the chemical composition and structure of which have not been determined. The microhardness of polymerized C60 is higher than that of single crystal samples roughly four-fold at room temperature and by a factor of 2.6 at liquid nitrogen temperature. Analysis shows that polymerization and grain boundaries give contributions to the microhardness of sintered samples but we did not succeed in separating these two contributions. The temperature dependence of the microhardness of polymerized samples exhibits a jump in the vicinity of 260 K, where pristine C60 fullerite undergoes the fcc-sc phase transition. We think that this jump is due to a partial destruction of the polymerized state under indentor as a result of shear straining in inhomogeneous stress fields. Annealing of polymerized C60 at a temperature of 573 K, which restores the fcc phase, leads to a considerable decrease in microhardness, the hardness &quotjump&quot near the fcc-sc transition extends in temperature and shifts to lower temperatures.